E-037 Single Center Comparison of Ophthalmic Aneurysm Treatment Using Pipeline Embolization Device Versus Coil Embolization. (26th July 2014) - Durst, C; Starke, R; Gingras, J; Hixson, H; Liu, K; Crowley, R; Jensen, M; Evans, A; Gaughen, J
Abstract : Introduction/purpose: Aneurysms arising from the ophthalmic segment of the internal carotid artery (ICA) account for approximately 5% of all intracranial aneurysms. The Pipeline Embolization Device (PED) is a relatively new device available for treatment of these aneurysms. Here, we compare our experience with PED versus coil embolization in the treatment of unruptured ophthalmic artery aneurysms. Materials and methods: A review of our prospectively collected patient log identified 106 patients who had undergone endovascular treatment of an unruptured ophthalmic artery aneurysm. Blinded to outcome, PED and coil patients were matched in a 1:2 fashion, respectively, based on aneurysm size. Matched analysis was carried out with marched t-test, Wilcoxon rank sum test, and McNamara's test as appropriate. P-values of ≤ 0.05 were considered statistically significant. Statistical analysis was carried out with Stata 10.0 (College Station, TX). Results: After matching the patients in a 1:2 fashion, there were 20 patients treated with PED and 40 treated by coil embolization. There were no statistically significant differences in age, sex, average aneurysm diameter, or maximum aneurysm diameter. There were significant differences between the two groups in length of follow up, phase of treatment, baseline mRS, presentation, and neck size. Morbidity was 2.5% in the coiled cohort and 10% in the PED cohort (p = 0.255). Note, however, that in 1 of the 2 complications in the PED group, the patient was not compliant with their dual anti-platelet therapy. Immediate occlusion rates favored coil embolization as would be expected. However, recurrences were more frequent in the coiled group (22 vs 0%, p = 0.046). Conclusions: This study suggests that complications may be more frequent with PEDs, but treatment may be more permanent as evidenced by the lower recurrence rate. Disclosures: C. Durst: None. R. Starke: None. J. Gingras: None. H. Hixson: None. K. Liu: None. R. Crowley: None. M. Jensen: 2; C; Covidien. A. Evans: 2; C; Covidien, Stryker. J. Gaughen: 2; C; Covidien, Stryker, Microvention.